Teachers’ Perception of Using Digital Game-Based Learning in Teaching and Learning Process - Engelina Salainti; Meily Ivane Esther Neman (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Technology is frequently utilized in modern classrooms to enrich the learning experience and facilitate diverse educational phenomena. In this age of technology, it is not uncommon to see technology used in almost every aspect of human life. Monotonous and old-fashioned teaching and learning activities make technology a fascinating aspect for teachers and even more so for students. Especially when technology is combined as an exciting and educational game that makes students feel a pleasant learning environment. DGBL (Digital Game-Based Learning) is a method that can be recommended to teachers. DGBL is a learning method that combines a fun learning method using games and technology. Students like technology especially when combined with games, which can excite them when learning. In this study, the researcher will explore how teachers from various subjects perceive using DGBL in their teaching and learning process. The quantitative data gathered from the respondents were analyzed through SPSS software. The findings indicate that teachers prefer using technological devices for better outcomes in the teaching and learning process. Teachers found that using game-based learning in their classrooms made students more engaged and motivated. This led to a better overall learning experience.